Analisa Kepuasan Konsumen Menggunakan Algoritma C4.5 - Nurul Azwanti; Erlin Elisa (Prosiding, 2020)
Consumer satisfaction is a very important measure for the sustainability of a business. One example is the business in the food sector. This business requires active consumers because it is related to consumer taste and satisfaction. Bakso Akbar as a business in the food sector certainly has many competitors. For the sustainability of this business, it is necessary to review what things make consumers satisfied and dissatisfied. One way is to analyze customer satisfaction with Service variables with Good or Not Good, Speed, Location Access with Easy or Difficult options, Cleanliness with Clean or Not options, Taste with Good, Not bad or Not good choices and the last one is Price with Expensive or Cheap stuffing. These variables will be filled in by consumers from the distributed questionnaires, which will then be recorded and processed using Data Mining. The C4.5 algorithm is considered to be one of the Data Mining algorithms that is able to give good results because it produces decision tree rules. The results showed that the Rasa variable got the first highest gain with a value of 0.3659. Subsequent calculations obtained the Cleanliness variable with a value of Gain 1. The resulting rule is 4, 2 rules resulting in a decision of Satisfaction with the condition if the taste is good, the consumer is satisfied and if the taste is good and the cleanliness is clean then the consumer is satisfied. The purpose of this analysis is so that the Bakso Akbar business can retain its customers and fix any shortcomings based on consumer assessments.